Gambaran Tingkat Pengetahuan Masyarakat Tentang Dagusibu di Desa Salubomba Kecamatan Banawa Tengah Kabupaten Donggala - Ikhsan Hi. Amir Sene; Nurfadilah Nurfadilah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Knowledge results from knowing and occurs when someone senses a particular object. Dagusibu (Get Use Save and Throw Away) is a health education program created by IAI (Indonesian Pharmacists Association) to create a Drug Aware Family Movement as a concrete step to improve the quality of life of the community. This research aims to determine the level of community knowledge about Dagusibu Medicine in Salubomba Village, Central Banawa District, Donggala Regency based on age, occupation, and education. The type of research is descriptive research. The population of the study is all people who live in Salubomba Village, Central Banawa District, Donggala Regency. The sample used was 94 people with each hamlet representing 19 people. The sampling technique uses purposive sampling. The results of the research showed that the level of public knowledge about Dagusibu Medicine in Salubomba Village was 39 respondents with poor knowledge, 51 respondents with sufficient knowledge, and 4 respondents with good knowledge. So, it can be concluded that the level of knowledge of the people in Salubomba Village has an adequate level of knowledge about Dagusibu Medicine. The conclusion that can be drawn is that the level of public knowledge about Dagusibu Medicine is sufficient knowledge, namely the level of public knowledge based on age level with less knowledge is 41.42%, based on occupation, less knowledge is 41.42%, and based on education, less knowledgeable is 41.48%.